Pengelolaan Pembelajaran Lesson Study Mata Pelajaran Ipa Di SMA Negeri 1 Nogosari Kabupaten Boyolali - Haryoto, Haryoto; Lestari, Marlupi Dwi; Suseno, Nugroho Adi (WIDYATAMA, 2010)
Pengelolaan Pembelajaran Lesson Study Mata Pelajaran Ipa Di SMA Negeri 1 Nogosari Kabupaten BoyolaliÂ Haryoto1), Marlupi Dwi Lestari2), Nugroho Adi Suseno3)Â 1)Staf Pengajar Progdi Magister Manajemen Pendidikan Program Pascasarjana Universitas Muhammadiyah Surakarta2)Guru Sekolah Menengah Atas Negeri 1 Nogosari, Kabupaten Boyolali3)Guru Sekolah Menengah Pertama Negeri 1, Kaliwungu, Kabupaten SemarangÂ AbstractÂ Quality of education in Nogosari High School still lower because there is use to function educational production approach which too centripetal at education input, less is paying attention of learning process, to increase quality of education conducted by real stages there are learning process of pass with lesson study approach. Learning process of lesson study is conducted represent learning process collaboration by teachers through three activities there are planning, implementation, and reflection. Planning is started identified the problem, analysis of problem, determination of problem priority to be solved, election the lesson model, making lesson plan, cozening method, physic appliance and assessment conducted together by collaboration. The implementation of lesson is conducted together, someone become teacher model and other is observation of learning process; observer may not bother of learning process, observer duty note important problem in lesson. The reflection is conducted after ending lesson, its analyzing learning process, teachersâ model submit what experienced by learning moment, while observer submit result of observation, then analyzed and looked for the way out of the problem of faced at the moment of lessonÂ  implementation. Learning Process of lesson study in Nogosari High School implemented by collaboration between âscience teacherâ and âstudy teacherâ which start planning until implementation, as for reflection is implemented every saturday of meeting learn or Team Working of Teacher. Result of learning for lesson study in Nogosari High School can improve the quality of education. Â Keywords: Lesson Study